Metformin Alleviates Obesity and Systemic Oxidative Stress in Obese Young Swine - Susana Astiz; Antonio Gonzalez-Bulnes; Isabel Astiz; Alicia Barbero; Jose Luis Pesantez-Pacheco; Consolacion Garcia-Contreras; Marta Vazquez-Gomez; Ana Heras-Molina (MDPI AG, 2020)
The present study assessed the relationship between obesity induced by lifestyle and systemic oxidative stress and possible modulations by oral metformin treatments in young individuals, by using a translational swine model of obesity and associated cardiometabolic disorders (Iberian pig). The results indicate the existence of an age-related increase in both adiposity and systemic oxidative stress (using hydrogen peroxide as a marker), which is higher in individuals with obesogenic lifestyle and increased weight and obesity. Such effect was not found in individuals treated with metformin. The translation of these results suggests that childhood obesity increases production of reactive oxygen species (ROS), and therefore systemic oxidative stress. Treatment with metformin would improve such oxidative status.